2017
DOI: 10.1186/s12940-017-0336-z
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer in firefighting and police work: a systematic review and meta-analysis of epidemiologic studies

Abstract: ObjectivesWe conducted a systematic review and meta-analysis to evaluate potential associations between firefighting and police occupations, and prostate cancer incidence and mortality.MethodsOriginal epidemiological studies published from 1980 to 2017 were identified through PubMed and Web of Science. Studies were included if they contained specific job titles for ever/never firefighting and police work and associated prostate cancer risk estimates with 95% confidence intervals (CI). Study quality was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 69 publications
6
50
0
1
Order By: Relevance
“…In another recent investigation, Sritharan et al reported the pooled risk of 1.17 (1.08 to 1.28; I 2 :72%) and 1.12 (0.92 to 1.36; I 2 : 50%) for incidence and mortality, respectively. 74 We found similar results for prostate cancer, with significantly elevated incidence, and nonsignificantly elevated mortality.…”
Section: And Sritharansupporting
confidence: 76%
See 1 more Smart Citation
“…In another recent investigation, Sritharan et al reported the pooled risk of 1.17 (1.08 to 1.28; I 2 :72%) and 1.12 (0.92 to 1.36; I 2 : 50%) for incidence and mortality, respectively. 74 We found similar results for prostate cancer, with significantly elevated incidence, and nonsignificantly elevated mortality.…”
Section: And Sritharansupporting
confidence: 76%
“…Totally, four peer-reviewed meta-analyses including Howe and Burch, 73 Youakim,15 LeMasters et al 14 74 have studied the association of firefighting occupation and some selected malignancies. We compared the current study findings with the recent and comprehensive studies conducted by Sritharan et al and LeMasters et al…”
Section: Comparison To Previous Meta-analysesmentioning
confidence: 99%
“…Some meta-analyses have examined the extent of cancer risk among firefighters before and did not find higher overall cancer incidence and mortality as expected (International Agency for Research on Cancer (IARC) 2010; Jalilian et al 2019;Sritharan et al 2017;Crawford et al 2017;LeMasters et al 2006;Youakim 2006;Howe and Burch 1990), although a few single studies reported elevated overall cancer risks (Daniels et al 2014;Glass et al 2016;Guidotti 1993;Pukkala et al 2014). However, meta-analyses found that firefighters were at increased risk of developing or dying from malignant melanoma of the skin (Jalilian et al 2019;Howe and Burch 1990), multiple myeloma (LeMasters et al 2006), mesothelioma (Jalilian et al 2019), digestive (Jalilian et al 2019;LeMasters et al 2006), prostate (Jalilian et al 2019;LeMasters et al 2006;Sritharan et al 2017), testicular (Jalilian et al 2019;LeMasters et al 2006), kidney (Youakim 2006), bladder (Jalilian et al 2019), and thyroid cancer (Jalilian et al 2019), as well as non-Hodgkin lymphoma (Jalilian et al 2019;Youakim 2006;LeMasters et al 2006).…”
Section: Introductionmentioning
confidence: 93%
“…In a meta-analysis of 31 studies, Sritharan et al (2017) evaluated the incidence and mortality risk of prostate cancer for firefighters and police officers. The analysis was based on studies published between 1980 and 2017.…”
Section: Comparisons With Policementioning
confidence: 99%